Water Extraction Optimization of Rice Leaf Extracts via Face-Centered Composite Design (FCCD) - Dwi Ayuni; Chaleeda Borompichaichairtkul (Universitas Muhammadiyah Purwokerto, 2025)
Rice leaves (Oryza sativa L.) contain a high concentration of bioactive compounds, particularly flavonoids and phenolics, which have potential applications in functional foods. This study aims to optimize the decoction process for extracting phenolic compounds from rice leaves using Response Surface Methodology (RSM). A Face-Centered Composite Design (FCCD) was applied to evaluate the impact of extraction parameters, including time and liquid-to-solid ratio, on total phenolic content (TPC) and antioxidant activities (FRAP, DPPH, ABTS). Results showed that the pH of the extracts remained stable (6–7) regardless of extraction conditions, while colorimetric analysis indicated that a lower liquid-to-solid ratio and prolonged boiling enhanced yellowness (b*) and chroma. The optimal extraction conditions determined through RSM were a boiling time of 30 minutes and a ratio of 37 mL/g, yielding maximum TPC and antioxidant activities. The model demonstrated statistical significance (p < 0.05), with high R² values (>0.9) and adequate precision (>4). Under these conditions, phenolic extraction efficiency improved by 3–7% compared to previous studies, while solvent usage was reduced by 7.5%. These findings confirm that optimizing decoction parameters enhances the efficiency of phenolic compound extraction while maintaining food-grade suitability, making it feasible for large-scale applications.